Challenges to Learner Autonomy in Online Speaking Classes: Insights from University Students in Indonesia - Dewi Warna; Rizqy Dwi Amrina; Ai Yeni Yulianti; Abdurrahmansyah Abdurrahmansyah; Muhamad Uyun (STAI Hubbulwathan Duri, 2025)
Although online English language learning has been widely praised for its flexibility and accessibility, its effectiveness in developing speaking skills—where learner autonomy is essential—remains underexplored. The COVID-19 pandemic necessitated a sudden shift to online formats, exposing significant challenges in how learners independently manage speaking practice. This qualitative study investigated the impact of online learning environments on learner autonomy in speaking classes. Data were collected through purposive sampling from two lecturers and twelve students at two state universities in Palembang, Indonesia. Semi-structured interviews were conducted and analyzed using thematic analysis to identify patterns in self-directed learning behavior. Analysis revealed five key barriers to learner autonomy in online speaking courses: (1) lack of goal-setting, (2) poor time management, (3) absence of structured study plans, (4) limited application of communication strategies during speaking tasks, and (5) minimal use of available learning resources. These interconnected issues suggest that current online formats fall short in supporting the autonomous development of speaking skills. The findings underscore the limitations of fully online learning in fostering autonomous language development, particularly in speaking. Learners often struggle without structured support and direct interaction. To enhance learner autonomy in speaking classes, a blended learning model is recommended. By integrating the flexibility of online tools with the engagement of face-to-face instruction, this approach provides a more supportive and balanced environment for autonomous learning.